Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study - Brauko, Kalina M.; Cabral, Alex; Costa, Natasha V.; Hayden, Juliana; Dias, Carlos E. P.; Leite, Edilene S.; Westphal, Renan D.; Mueller, Carolina M.; Hall-Spencer, Jason M.; Rodrigues, Regina R.; Rörig, Leonardo R.; Pagliosa, Paulo R.; et al. (Frontiers in Marine Science, 2020)
Marine heatwaves are becoming a major concern worldwide because of due to their increasing impacts in recent years, and it seems likely that these extreme events could trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of marine heatwaves, organic pollution and plus nutrient enrichment on the biogeochemical processes and the marine biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994-2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to evaluate assess temporal trends. During the austral summer of 2020 a regional sea surface heatwave was detected by satellite, persisting for 9 days and coinciding with our research cruise. During this period, seawater temperatures in the bay reached 29.8°C and became hypoxicanoxic events were measured for the first time. Long-term data show that oxygen Oxygen levels have been decreasing whilst phosphorus levels have been increasing in the bay. A decrease in macrobenthic and phytoplankton community richness correlates with decrease in oxygen both through time and towards more urbanized areas. Overall, poor wastewater treatment is a key stressor that combined with marine heatwaves to degrades coastal waters. Mitigation strategies are needed to minimize the impact of these warm events, including improved sewage treatment, restoration and conservation of wetlands and the implementation of nature-based technologies to promote coastal ecosystem recovery.